YOUTH OLYMPIC GAMES IN THE SYSTEM OF OLYMPIC SPORTS COMPETITIONS - Кузнєцова, Олена; Кособуцький, Юрій; Пасевич, Анатолій; Дворак, Вероніка (SWorldJournal, 2025)
The paper examines the features of the organization, conduct and results of the participation of the national team of Ukraine in the Youth Olympic Games. Purpose: to analyze the results of the participation of the national team of Ukraine in the Youth Ol